Analisis Program Pemberian Makanan Tambahan (PMT) Terhadap Perbaikan Status Gizi Ibu Hamil di Daerah Rawan Stunting - Nursiah, Andi; Treasa, Adisty Dwi; Fitri, Lidia; Srifitayani, Nur Rahma; Subani, Natalia Debi; Yermi, Yermi (Barongko: Jurnal Ilmu Kesehatan, 2025)
Background: Chronic Energy Deficiency (CED) in pregnant women is a major risk factor contributing to stunting in children. A local food-based supplementary feeding (PMT) program has been implemented in several stunting-prone areas as a promotive-preventive strategy to improve the nutritional status of pregnant women. Objective: To analyze the effectiveness of the local food-based PMT program in reducing the prevalence of CED among pregnant women in stunting-prone areas. Methods: This quantitative study used a quasi-experimental pre-post test design without a control group. Subjects were 60 pregnant women in their second and third trimesters in the intervention area. Data were collected through measurements of mid-upper arm circumference (MUAC), body mass index (BMI), and nutritional intake questionnaires over a 3-month period. Results: There was a significant increase in mean MUAC from 22.8 cm to 24.1 cm (p<0.05), as well as an increase in daily energy and protein intake based on a 24-hour food recall. A total of 68.3% of respondents who were initially at risk of CED experienced improvements in nutritional status after the program was implemented. Conclusion: The local food-based PMT program is effective in reducing the risk of chronic energy deficiency syndrome (CED) and improving the nutritional status of pregnant women. Recommendations include integrating PMT into routine integrated health post (Posyandu) policies and sustainable use of local food resources.